Learning Microsoft Exchange Server 2013 - Long, Mark (InfiniteSkills, 2014)
"In this Microsoft Exchange Server 2013 training course, expert author Mark Long teaches you the fundamentals of the latest version of Exchange. This course is designed for the absolute beginner, meaning no previous experience with Exchange is required. You will start by learning the basics of Exchange, including how it works, the terminology, and mail flow. You will then learn about the active directory, administration center, and the basics of database maintenance. Mark will teach you mailbox basics, public folders, and how to manage Exchange data. This video tutorial will also teach you client access basics and configuration."--Resource description page.
Title from resource description page (viewed Feb. 24, 2014)
Keywords: Microsoft Exchange server; Client/server computing; Electronic mail systems; Electronic Mail; Architecture client-serveur (Informatique); Courrier électronique; electronic mail; Electronic videos